Fethullah Gülen : interfaith dialogue as a way to the global peace - Ahmad Sunawari Long,; Mohd. Hatib Ismail,; Zul`azmi Yaakob, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Fethullah Gülen is an authoritative mainstream Turkish Muslim scholar, thinker, and educational activist who supports interfaith and intercultural dialogue. He is opposed to violence and to turning religion into a political ideology. In Turkey, he has been credited for bringing about positive atmospheres between the Muslim population and the various religious minorities such as the Christian and Jewish communities. Outside Turkey, his ideas on interfaith dialogue have inspired many to establish organizations engaging in dialogue with the same objectives of mutual understanding, empathetic acceptance, peaceful coexistence, and cooperation. He has outlined four main foundations in his dialogue, namely, love, compassion, tolerance, and forgiveness, as a form of a religious order which is known as the universal values. He has introduced two types of practical dialogue, which are the dialogue through mass media and the dialogue through educational institutions, which aim to create a better understanding between the Muslims and non-Muslims among the Golden Generations. Over the years, Gülen is a champion of interfaith dialogue who has been committed to bringing global peace beyond the boundary of religion, race, and region.